Case report: Complications after using the “blind-stitch” method in a dairy cow with a left displaced abomasum: treatment, outcome, and economic evaluation - Schären-Bannert, Melanie; Bittner-Schwerda, Lilli; Rachidi, Fanny; Starke, Alexander (Frontiers in Veterinary Science, 2024)
A fourth lactation dairy cow that was 35 days in milk was referred to the clinic for treatment after undergoing unsuccessful treatment of a left displaced abomasum (LDA). The physical examination revealed complications after using the “blind-stitch” method for correction of the LDA; the cow had an abnormal general demeanor, decreased gastrointestinal motility, and local inflammation of the abdominal wall at the site of the suture. Systemic antibiotics, anti-inflammatory drugs, and intravenous fluids were administered, and a right flank laparotomy and omentopexy according to Dirksen were performed after cutting the suture and breaking down the adhesions of the localized peritonitis between the abdominal wall and the abomasal puncture site. The cow was monitored clinically and discharged 2 weeks after referral. The cow was milked for another two lactations producing a total of 18,000 kg of milk, with a lifetime production of 59,141 kg. The total cost for the case was 310 € for the first intervention using the “blind-stitch” method and 897 € for the second laparotomic intervention. The costs (excluding tax) of both procedures including physical examination, surgery, medications, diagnostics, and labor were calculated. The lost revenue associated with the withdrawal period and lower milk production was 4,168 €. Percutaneous LDA fixation techniques, such as the “blind-stitch” and “toggle-pin” methods, have gained popularity because they are quick and cost-effective and involve minimal labor. However, many buiatricians are critical of these techniques because of the high risk of complications. The following four factors require careful consideration when choosing a method for LDA correction: (1) Percutaneous methods require precision and adherence to the described inclusion, exclusion, and cancelation criteria; (2) Operator skill is essential, and therefore regularly performing laparotomies increases surgical experience and enables the veterinarian to better manage different and more complex abdominal disorders; (3) By performing a laparotomy, other underlying abdominal disorders such as reticuloperitonitis and abomasal ulcers may be detected; (4) Postoperative husbandry and treatment are important factors affecting the outcome. The cost calculated for this case underlines the potential benefit and necessity of successful animal health management and the importance of a highly skilled veterinarian and farm workforce.